2001
DOI: 10.1021/ol015850d
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Aryl Chlorides for Suzuki Cross-Coupling by Ligandless, Heterogeneous Palladium

Abstract: We demonstrate that Pd/C without added ligands catalyzes the Suzuki cross-coupling reaction with aryl chlorides. The ability of heterogeneous Pd to activate the C−Cl bond is explained in terms of a synergistic anchimeric and electronic effect that occurs between the Pd surface and the aryl chloride. Furthermore, the importance of selectivity control following C−Cl bond activation is illustrated by the striking role that solvents play in determining homo- vs cross-coupling pathways of the aryl chlorides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
140
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(142 citation statements)
references
References 31 publications
1
140
0
1
Order By: Relevance
“…The catalytic activity of PdAS for the heterogeneous Suzuki-Miyaura reaction [76][77][78][79][80][81][82][83][84][85][86][87][88][89] was investigated (Table 5). Since "water" is the most safe, non-toxic, and easily available solvent, numerous attempts have been made in utilizing it to the organic reactions.…”
Section: Catalytic Activity Of Pdas For the Suzukimiyaura Reactionmentioning
confidence: 99%
“…The catalytic activity of PdAS for the heterogeneous Suzuki-Miyaura reaction [76][77][78][79][80][81][82][83][84][85][86][87][88][89] was investigated (Table 5). Since "water" is the most safe, non-toxic, and easily available solvent, numerous attempts have been made in utilizing it to the organic reactions.…”
Section: Catalytic Activity Of Pdas For the Suzukimiyaura Reactionmentioning
confidence: 99%
“…It was demonstrated that a Pd/C catalyzed Suzuki crosscoupling reactions of activated chloroarenes with various arylboronic acids were possible upon fine adjustment of the DMA/water ratio [72]. However, these reactions were performed at high Pd concentrations (5 mol%) and over long reaction times (24 h).…”
Section: Suzuki-miyaura Reactions Of Aryl Chloridesmentioning
confidence: 99%
“…167 Some other interesting results about Suzuki cross-coupling reactions catalysed by Pd on carbon have been described. 135,[169][170][171] For instance, this heterogeneous catalyst proved to be able to catalyse the Suzuki reaction with aryl chlorides at 80°C in a 20:1 mixture of dimethylacetamide and water, in the presence of K 2 CO 3 as the base. 170 The ability of heterogeneous Pd to activate the C-Cl bond was explained in terms of a synergistic anchimeric and electronic effect that occurs between the Pd surface and the aryl chloride.…”
Section: Scheme 12mentioning
confidence: 99%
“…170 The ability of heterogeneous Pd to activate the C-Cl bond was explained in terms of a synergistic anchimeric and electronic effect that occurs between the Pd surface and the aryl chloride. 170 On the other hand, a specially optimised air-stable Pd on activated carbon catalyst (i.e. E 105 CA/ W 5% Pd, product of Degussa AG) was demonstrated to be a highly active (TON up to 36,000), selective and heterogeneous catalyst for cross-couplings of phenylboronic acid with aryl bromides or activated aryl chlorides.…”
Section: Scheme 12mentioning
confidence: 99%